[(18)F]CFA as a clinically translatable probe for PET imaging of deoxycytidine kinase activity - Kim, Woosuk (Proc Natl Acad Sci U S A, 2016)
Deoxycytidine kinase (dCK), a rate-limiting enzyme in the cytosolic deoxyribonucleoside (dN) salvage pathway, is an important therapeutic and positron emission tomography (PET) imaging target in cancer. PET probes for dCK have been developed and are effective in mice but have suboptimal specificity and sensitivity in humans. To identify a more suitable probe for clinical dCK PET imaging, we compared the selectivity of two candidate compounds—[(18)F]Clofarabine; 2-chloro-2′-deoxy-2′-[(18)F]fluoro-9-β-d-arabinofuranosyl-adenine ([(18)F]CFA) and 2′-deoxy-2′-[(18)F]fluoro-9-β-d-arabinofuranosyl-guanine ([(18)F]F-AraG)—for dCK and deoxyguanosine kinase (dGK), a dCK-related mitochondrial enzyme. We demonstrate that, in the tracer concentration range used for PET imaging, [(18)F]CFA is primarily a substrate for dCK, with minimal cross-reactivity. In contrast, [(18)F]F-AraG is a better substrate for dGK than for dCK. [(18)F]CFA accumulation in leukemia cells correlated with dCK expression and was abrogated by treatment with a dCK inhibitor. Although [(18)F]CFA uptake was reduced by deoxycytidine (dC) competition, this inhibition required high dC concentrations present in murine, but not human, plasma. Expression of cytidine deaminase, a dC-catabolizing enzyme, in leukemia cells both in cell culture and in mice reduced the competition between dC and [(18)F]CFA, leading to increased dCK-dependent probe accumulation. First-in-human, to our knowledge, [(18)F]CFA PET/CT studies showed probe accumulation in tissues with high dCK expression: e.g., hematopoietic bone marrow and secondary lymphoid organs. The selectivity of [(18)F]CFA for dCK and its favorable biodistribution in humans justify further studies to validate [(18)F]CFA PET as a new cancer biomarker for treatment stratification and monitoring.